Quantifying competitive swim training using accelerometer-based activity monitors - Wright, B. V.; Stager, J. M. (Sports Engineering, 2013)
Recent advances in miniaturized waterproof accelerometers have allowed their use as a tool in examining swim stroke characteristics (Ohgi et al. JPSE Int J 45:960-966, 2002; Sports Eng 6:113-123, 2003). A better use for this technology, however, might be to quantify characteristics of competitive swim training. The purpose of this study was thus to examine commercial accelerometers` ability to track and quantify swim training variables common to all swim training programs: speed and distance. Swimmers (n = 43) were fitted with two accelerometer monitors on their right wrist and ankle. From this output, regression analyses were performed as a means to describe swim distance and speed. Ten additional swimmers (experimental group, n = 10) were then utilized to cross validate these equations as being useful to predict swim distance and speed. The results demonstrated a positive, significant relationship between activity counts and actual swim distance (r = 0.90, p < 0.05), actual swim speed (r = 0.80; p < 0.05), and cross validation confirmed the accuracy of the prediction equations. The findings of the present study suggest that commercial accelerometer-based activity monitors have the ability to quantify important characteristics of competitive swim training.